Pathologic Factors Associated with Prognosis after Adjuvant Chemotherapy in Stage II/III Microsatellite-Unstable Colorectal Cancers - Jung Ho Kim; Jeong Mo Bae; Hyeon Jeong Oh; Hye Seung Lee; Gyeong Hoon Kang (Korean Society of Pathologists & the Korean Society for Cytopathology, 2015)
Background: Although there are controversies regarding the benefit of fluoropyrimidine-based adjuvant chemotherapy in patients with microsatellite instability-high (MSI-H) colorectal cancer (CRC), the pathologic features affecting postchemotherapeutic prognosis in these patients have not been fully identified yet. Methods: A total of 26 histopathologic and immunohistochemical factors were comprehensively evaluated in 125 stage II or III MSI-H CRC patients who underwent curative resection followed by fluoropyrimidine-based adjuvant chemotherapy. We statistically analyzed the associations of these factors with disease-free survival (DFS). Results: Using a Kaplan- Meier analysis with log-rank test, we determined that ulceroinfiltrative gross type (p=.003), pT4 (p<.001), pN2 (p=.002), perineural invasion (p=.001), absence of peritumoral lymphoid reaction (p=.041), signet ring cell component (p=.006), and cribriform comedo component (p=.004) were significantly associated with worse DFS in patients receiving oxaliplatin-based adjuvant chemotherapy (n=45). By contrast, pT4 (p<.001) and tumor budding-positivity (p=.032) were significant predictors of poor survival in patients receiving non-oxaliplatin-based adjuvant chemotherapy (n=80). In Cox proportional hazards regression model-based univariate and multivariate analyses, pT category (pT1-3 vs pT4) was the only significant prognostic factor in patients receiving non-oxaliplatin-based adjuvant chemotherapy, whereas pT category, signet ring cell histology and cribriform comedo histology remained independent prognostic factors in patients receiving oxaliplatin-based adjuvant chemotherapy. Conclusions: pT4 status is the most significant pathologic determinant of poor outcome after fluoropyrimidine-based adjuvant chemotherapy in patients with stage II/III MSI-H CRC.